Counting the Cost of Cervical Collars. Issue 6 (7th November 2017) - Veljanoski, Damjan; Grier, Gareth; Wilson, Mark H.
Abstract : D Veljanoski, G Grier, MH Wilson .Counting the cost of cervical collars .Prehosp Disaster Med .2017 ;32 (6 ):701 –702 .